Integrating Science and Technology in Islamic Education through the Tawhid Paradigm - Muhammad Hizba Aulia; Aam Abdussalam; Aceng Kosasih; Ahmad Dimyati Ridwan; Muhamad Mauris Faruqi Ali; Achmad Ghiyats Setiawan; M. Nur Faizin (Mauriduna : Journal of Islamic Studies, 2025)
This study examined the implementation of the tawhid paradigm as an epistemological foundation for integrating science and technology within Islamic education, aiming to address knowledge dichotomy, fragmentation, and curriculum stagnation prevalent in many Islamic educational institutions. Positioned within the framework of Islamic epistemology, this qualitative research adopted a library study design within an interpretative paradigm. Data were obtained from credible scholarly sources such as journal articles, books, and conference papers, and analyzed through descriptive–qualitative content analysis based on the Miles and Huberman model. The findings indicated that the tawhid paradigm underpins three main integration models: interconnection, Islamization of knowledge, and a holistic framework, which collectively strengthen the relationship between academic knowledge, practical expertise, and the development of learners’ spiritual and moral character. This study proposed a synthetic approach emphasizing the systematic and contextual and practical application of these models to foster an ethical and character-driven Islamic scientific civilization. The tawhid paradigm is identified as a strategic foundation for cultivating knowledgeable, ethical individuals capable of contributing meaningfully to the development of a just, civilized, and beneficial society.